Ecology of the East Pacific green turtle (Chelonia mydas) at Virrila Estuary, northern coast of Peru: conservation and management implications - Paredes Coral, Evelyn (2017)
Thesis submitted in partial fulfillment for master degree in Marine and Lacustrine Science and Management.